1996
DOI: 10.1017/s0813483900003922
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Management in Primary Schools: A Review of the Literature

Abstract: A considerable body of classroom management research has attempted to examine teacher and student variables believed to correlate with student academic achievement. However, only some of these variables are alterable by the school. Knowledge of these alterable variables may assist schools to make informed decisions about managing primary school classrooms to maximise student achievement. Evidence suggests that students' activity (level of academic engaged time and academic learning time) may be causally interm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 56 publications
1
17
0
Order By: Relevance
“…Although there is consistency between the findings of the present study and the results of previous studies (Rickman & Hollowell, 1981;Osbourne & Boisvert, 1989;Wragg, 1993;Akkök et al, 1995;Tulley & Chiu, 1995;Wilks, 1996;Mau, 1997;Jones & Jones, 1998;Atıcı, 1999;Tü rnü klü , 1999;Atıcı, 2004) the comments made in the study are not generalized beyond the context in which the study is carried out.…”
Section: Participantssupporting
confidence: 51%
See 1 more Smart Citation
“…Although there is consistency between the findings of the present study and the results of previous studies (Rickman & Hollowell, 1981;Osbourne & Boisvert, 1989;Wragg, 1993;Akkök et al, 1995;Tulley & Chiu, 1995;Wilks, 1996;Mau, 1997;Jones & Jones, 1998;Atıcı, 1999;Tü rnü klü , 1999;Atıcı, 2004) the comments made in the study are not generalized beyond the context in which the study is carried out.…”
Section: Participantssupporting
confidence: 51%
“…Consistent with the related literature (Brophy & Evertson, 1976;Wilks, 1996;Jones & Jones, 1998) the student teachers' perception of classroom management can be summarised under the main topics of instructional management, behaviour management, communication, and physical organization of the classroom. The kinds of misbehaviour experienced by student teachers are similar to the research results in existing literature, especially in terms of talking out of turn, being noisy, disturbing others, inattentiveness, chatting and inappropriate movement (Wragg & Dooley, 1984;Wragg, 1993;Akkök et al, 1995;Tulley & Chiu, 1995;Mau, 1997;Atıcı, 1999;Tü rnü klü , 1999;Atıcı, 2004).…”
Section: Discussionmentioning
confidence: 64%
“…In an effectively managed classroom, more time is allocated to learning activities and pupils spend their time actively involved in particular learning tasks and they also learn how to manage themselves through classroom management (Wilks, 1996). Wheldall and Merrett's (1988) study confirmed these assumptions.…”
Section: Introductionmentioning
confidence: 68%
“…The literature revealed that especially at primary level, teachers mostly encounter minor behaviour problems like talking out of turn, disturbing others, inattentiveness rather than serious or major ones (Wragg and Dooley, 1984;Wragg, 1993;Merrett and Wheldall, 1987;Johnson et al, 1993;Akkok et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In an effectively managed classroom, more time is spent on learning activities and students participation to the class is increased. Thus, increase of success is ensured for students [3]. So, a contemporary class management system that is student based is developed.…”
mentioning
confidence: 99%